An Analysis of Deixis in Leo Movie (2023) - Paundrianagari, Kinanti Dwiqalsa; Harida, Ratri (SALIENCE: English Language, Literature, and Education Journal, 2024)
Deixis in movies is often used to create a sense of immersion for the audience. The intricate layers of deixis help to establish a strong connection between the audience and the characters. There are five main types of deixis: person deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis. Each type serves a specific purpose in guiding the audience’s understanding of the narrative and enhancing their overall viewing experience. This qualitative descriptive research aimed to find five different forms of deixis in Leo. Through note taking techniques and data analysis, it was found that personal deixis occurs more than other types of deixis. It was then followed by the occurrence of temporal/time and social deixis. Social and discourse deixis, which are the least common types of deixis, are also very important in raising the film’s emotional impact and storytelling.